Power efficient ultra-wideband radio frequency identification tag with time hopping - Ang, Boon Ping (2009)
This project aims to develop a power efficient Ultra-Wideband (UWB) Radio Frequency Identification (RFID) active tag (transmitter) with time hopping capability. The power efficient active tag is achieved by using amplifiers with power down features by turning them ‘ON’ and ‘OFF’ as and when there are inputs to the amplifiers. This can be achieved by sending very narrow (10ns) and precise square pulses to turn ‘ON’ the amplifiers just before the arrival of the UWB Gaussian pulse. In addition, applications such as tracking human location or body movement can be achieved with the time hopping capability. The main objective of this project is to develop and integrate the power down circuit; programmable delay chip; microcontroller MSP430 and the active tag (transmitter) to achieve power efficient pulse to be detected and differentiated by the receivers using time hopping - Code Division Multiple Access (CDMA). The scope of this project involves the understanding of the impulse radio UWB, RFID, time hopping - CDMA, circuit design and hardware fabrications. With the theoretical knowledge, the prototype is designed and the Printed Circuit Board (PCB) is created using Advanced Design System 2006A (ADS). The milling machine was used for fabrications and the components were then soldered onto it. In addition, the microcontroller is programmed to output ‘1’s and ‘0’s (codes) into the programmable delay chips to have different delays to achieve time-hopping. Lastly, testing, trouble-shooting and verifications of the outputs at different stages are done. In conclusion, the power reduction technique and multiple access control were implemented on the active tag and was built and tested. The time hopping sequence was also implemented and recommendation on ways to achieve higher output voltage (Vp-p) and further reduction of current consumption was suggested.